EPISTEMOLOGY OR THE THEORY OF KNOWLEDGE - Coffey, P. (1917)
CONTENIDO: V.1 T.1 THE NATURE OF THE INQUIRY.-- V.1 T.2 INTELLECTUAL KNOWLEDGE: JUDGMENT.-- V.1 T.3 INTELLECTUAL KNOWLEDGE: CONCEPTION.-- V.2 T.4 THE DATA OF INTELLECTUAL KNOWLEDGE; SENSE PERCEPTION.-- V.2 T.5 TRUTH AND CERTITUDE: THEIR CRITERIA AND MOTIVES